Ancient evolution of hepadnaviral paleoviruses and their impact on host genomes. Issue 1 (3rd March 2021) - Lytras, Spyros; Arriagada, Gloria; Gifford, Robert J
Abstract: Hepadnaviruses (family Hepadnaviviridae ) are reverse-transcribing animal viruses that infect vertebrates. DNA sequences derived from ancient hepadnaviruses have been identified in the germline genome of numerous vertebrate species, and these 'endogenous hepatitis B viruses' (eHBVs) reveal aspects of the long-term coevolutionary relationship between hepadnaviruses and their vertebrate hosts. Here, we use a novel, data-oriented approach to recover and analyse the complete repertoire of eHBV elements in published animal genomes. We show that germline incorporation of hepadnaviruses is exclusive to a single vertebrate group (Sauria) and that the eHBVs contained in saurian genomes represent a far greater diversity of hepadnaviruses than previously recognized. Through in-depth characterization of eHBV elements, we establish the existence of four distinct subgroups within the genus Avihepadnavirus and trace their evolution through the Cenozoic Era. Furthermore, we provide a completely new perspective on hepadnavirus evolution by showing that the metahepadnaviruses (genus Metahepadnavirus ) originated >300 million years ago in the Paleozoic Era and have historically infected a broad range of vertebrates. We also show that eHBVs have been intra-genomically amplified in some saurian lineages, and that eHBVs located at approximately equivalent genomic loci have been acquired in entirely distinct germline integration events. These findings indicate that selective forces have favoured the accumulation of hepadnaviral sequences at specific loci in the saurian germline. Our investigation provides a range of new insights into the long-term evolutionary history of reverse-transcribing DNA viruses and shows that germline incorporation of hepadnaviruses has played a role in shaping the evolution of saurian genomes.